Struktur Benih dan Dormansi pada Benih Panggal Buaya (Zanthoxylum rhetsa (Roxb.) D.C. (Structure and Dormancy of Panggal Buaya Seed (Zanthoxilum rhetsa (Roxb.) D.C.)) - Diyah Purwaning (Jurnal Manajemen Hutan Tropika, 2009)
Panggal buaya (Zanthoxilum rhetsa (Roxb.) D.C.) is generally used as raw material of wooden craft industry, because it has smooth texture with interesting color and it is also easy to process using both hand and machine. In order to anticipate the raw material insufficiency, panggal Buaya planting is very important. However, the resistance faced in the panggal Buaya stand development was the difficulty of it’s germination.  The information on its cultivation and seed management are still very limited. The other problems on its development was plant propagation which was caused by the existence of seed coat dormancy. This research was aimed to know the cause of seed coat dormancy on panggal buaya seed through lignin contents at seed coat and seed coat structure microscopically, and then, to know effective dormancy faulting treatment and finally, to learn the effect of this treatment to the microscopic structure of panggal buaya seed coat. The research shows that submerging the panggal buaya seed in sulfate acid 95%  as long as 30 minutes that follow the submerging it in water which has room temperature for along 1 x 24 hours could  stop the dormancy of the seed (grow potential 40,7%, germination capacity 39,7% and growing rapidity 0,698% KN etmal-1). Presumably, the faulting mechanism of dormancy is caused by the damage of cell wall of coat seed through lignin dissolving process by sulfate acid (delignification).Keywords: panggal buaya, seed dormancy, germination, delignification